Effect of interval from induction of puberty to initiation of a timed AI protocol on pregnancy rate in Nellore heifers - Rodrigues, A. D. P. [UNESP]; Peres, R. F. G. [UNESP]; Lemes, A. P.; Martins, T. [UNESP]; Pereira, M. H. C. [UNESP]; Carvalho, E. R. [UNESP]; Day, M. L.; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2014)
Prepubertal Bos indicus heifers (n = 774) were submitted to an E-2/P-4-based timed artificial insemination (TAI) protocol at three different intervals after induction of their pubertal ovulation by insertion of an intravaginal progesterone (P-4) device for 12 days. Heifers were randomly assigned to start the TAI protocol at 10 (group 10; n = 253), 12 (group 12; n = 265), or 14 (group 14; n = 256) days after the P4 device was removed. The TAI protocol consisted of the following: insertion of intravaginal device containing P4 (Controlled internal drug release [CIDR]; previously used twice for 9 days each) + estradiol benzoate (2 mg) on Day 0, CIDR withdrawal + estradiol cypionate (0.5 mg) and PGF2 alpha (12.5 mg) on Day 9, and TAI on Day 11. A subgroup of heifers (n = 472) was evaluated by ultrasound on Days 9 and 11 to evaluate the ovaries and to determine P4 concentrations on Day 9. On Day 9, more (P < 0.05) CLs were present, and follicular diameter was smaller (P < 0.05) for group 10 than for groups 12 and 14 (38.4%, 293%, and 23.3% with CL and 9.4 +/- 0.1, 9.9 +/- 0.1, and 9.8 +/- 0.1 mm diameter, respectively), but P4 concentrations did not differ (P > 0.1) between treatments (2.4 +/- 0.06 ng/mL). Follicular diameter at TAI (11.08 +/- 0.09 mm) and ovulation rate (88.4%) did not differ between treatments (P > 0.1). However, conception and pregnancy rates for all heifers were greater (P < 0.05) in group 12 (50.4% and 45.5%, respectively) than in group 10 (38.2% and 33.7%, respectively), with group 14 intermediate to other treatments (45.6% and 40.6%, respectively). The final pregnancy rate did not differ between treatments (80.9%). In conclusion, a 12-day interval from the end of the puberty induction protocol to the start of the TAI protocol resulted in greater conception and pregnancy rates in prepubertal Nellore heifers. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Prepubertal; Bos indicus; Heifers; TAI programs